Sustainable fabrication of introgen-doped carbon quantum dots from elaeis guineensis empty fruit bunches for solar photocatalysis towards organic dyes - Abd Rani, Umairah (2023)
Empty fruit bunches (EFB) are one of the palm oil mill’s most abundant sources of agricultural waste. Even though EFB has a high carbon, oxygen and hydrogen content, they are not well-explored for fabricating carbon-based nanoparticles. This study introduces a sustainable approach to fabricate nitrogen-doped carbon quantum dots (NCQDs) through hydrothermal treatment using lignin extracted from EFB as a raw material. The performance and stability of the fabricated NCQDs from EFB were evaluated through photocatalysis. This study discusses the photocatalytic degradation of methyl green dye using NCQDs through the Taguchi approach. At room temperature and methyl green dye solution of pH 7, functionalized NCQDs performed as effective photocatalysts in degrading 99% of methyl green dye under UV-light irradiation (302 nm) within 20 min. The average particle size of NCQDs was found to be 3.4 nm. The NCQDs showed greenish-blue fluorescence under a UV lamp owing to their excellent optical properties and the optical properties of NCQDs remained unchanged after several hours of UV-light exposure. NCQDs fabricated from EFB showed outstanding stability and reactivity in which they could retain their photocatalytic capability by storing at 5 ºC for twelve months. Around 99% of methyl green dye could be degraded in the first cycle and the NCQDs could be reused in photocatalysis for at least five repeated cycles while maintaining their photo-degradability of methyl green at above 70%. The NCQDs produced from EFB successfully degraded 98% of malachite green, 97% of methylene blue and 50% of methyl orange within 120, 180, and 300 min of sunlight irradiation, respectively. The photocatalytic degradation rate of methylene blue and malachite green dyes followed firstorder kinetics based on the Langmuir-Hinshelwood model. Meanwhile, the kinetic rate of degradation for methyl green dye followed the pseudo-secondorder model. NCQDs fabricated from EFB biomass show great potential and stability in treating wastewater contaminated with organic dyes.